In-flight food delivery and waste collection service: the passengers perspective and potential improvement - Romli, Fairuz Izzudin; Abdul Rahman, K.; Ishak, F. D. (Institute of Physics Publishing, 2016)
Increased competition in the commercial air transportation industry has made service quality of the airlines as one of the key competitive measures to attract passengers against their rivals. In-flight services, particularly food delivery and waste collection, have a notable impact on perception of the overall airline's service quality because they are directly and interactively provided to passengers during flight. An online public survey is conducted to explore general passengers' perception of current in-flight food delivery and waste collection services, and to identify potential rooms for improvement. The obtained survey results indicate that in-flight service does have an effect on passengers' choice of airlines. Several weaknesses of the current service method and possible improvements have been established from the collected responses.